Endocytic signaling in leaves and roots: same rules different players - Craddock, Christian; Yang, Zhenbiao (Frontiers in Plant Science, 2012)
To take up proteins and other components required by the cell, cells internalize a portion of the plasma membrane, which invaginates to form a closed vesicle within the cytoplasm in a process known as endocytosis. The major plant endocytic mechanism is mediated by clathrin, a protein that is necessary to generate a coated vesicle on the inner side of the plasma membrane. These vesicles bud away from the membrane generating a vesicle whose contents originated from outside of the cell and they can selectively concentrate or exclude compounds. The process is therefore of key importance to plant growth, development, signaling, polarity, and nutrient delivery. Rho family small GTPases are conserved molecular switches that function in many signaling events. Plants possess only a single Rho-like GTPase (ROP) family. ROPs are known to be involved in controlling cell polarity via the regulation of endocytosis. To contend with the high levels of regulation required for such processes, plants have evolved specific regulators, including the Rop-interactive CRIB motif-containing protein (RIC) effectors. Recent findings have demonstrated that ROP dynamics and the cytoskeleton (including actin microfilaments and microtubules) are interwoven. In this review we summarize the current understanding of endocytosis in plants, with particular regard to the signaling pathways involved.